SULTAN MUHAMMAD BELLO SENSE OF GOVERNANCE AND SHAYKH UTHMAN FUDOYE UNDERSTANDING OF ISLAMIC PRINCIPLES OF GOVERNMENT IN KITAB SARD AL-KALAM FIMA JARA BAYNI/BAYNANA WA BAINA ABD AL-SALAM AND KITAB AL-FARQ - Abubakar Muhammad Bala; Muhammad Sulaiman (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
Sokoto jihad literature seem to be the only literature in Nigeria, written by group of scholars that happen to be comprehensive in nature that covers every part of human endeavor the paper outlines the document of Islamic principle of leadership understand by shaykh Uthman bn Foduye. The books show the differences between the unbeliever’s system of government before the jihad and the Muslims system of government after the jihad. It also highlights the misunderstanding between Abdussalam who is happen to be shaykh’s student and either shaykh himself and or Muhammad Bello. The paper also concludes by recommending to the three group of people individual scholars, sultanate council and government in general to act appropriately for the re-introducing Sokoto Jihad literature to the Muslim community. The paper adopted secondary data in writing the research with the selection of the two books written by Shaykh Uthman bn Fudoye and Muhammad Bello which are Kitab Sard Al-Kalam Fima Jara Bayni/ Baynana Wa Baina Abd Al-Salam and Kitab Al-Fara.